White supremacy in eurocentric epistemologies : on the West’s responsibility for its philosophical heritage - Freter, Björn (Array, 2019)
There is a largely overlooked fundamental flaw in the Eurocentric epistemological foundation. Counter to the overwhelming ethos of the Enlightenment, this epistemological bedrock shockingly does not seem to be an epistemology of the human being, but only of the white human being. I, as a Western scholar, have to relativise my epistemological heritage, because it does not take into account the diversity of the human being. I will briefly explore the racist views of Voltaire, Hume, and Kant and I will argue that Western philosophy needs to (re)analyse its epistemological tradition with regards to the way the racist views of its protagonists corrupted their philosophical work. I suggest contextualization of the philosophical tradition and its desuperiorisation to foster ethical and broader philosophical dialogue amongst global scholars.